Trade Reform and Regional Integration in Africa. (International Monetary Fund, 1998)
Edited by Zubair Iqbal and Mohsin Khan, this volume is a collection of papers given at a seminar on trade issues in Africa, conducted by the IMF nad the African Economic Research Consortium. It represents the views of government officials, academics, and representatives from multilateral and regional agencies on issues relating to trade reform and regionalism in Africa. Issues include the role of trade liberalization in promoting sustained growth, interdependence of trade and macroeconomic policies, impediments to effective trade reforms, the steps needed to accelerate trade reform, and the importance of regional interaction.